Coxiella burnetii infection in humans: to what extent do cattle in infected areas free from small ruminants play a role?. (2020) - Pouquet, M.; Bareille, N.; Guatteo, R.; Moret, L.; Beaudeau, F.
Abstract: Domestic ruminants (cattle, goats and sheep) are considered to be the main reservoirs for human Coxiella burnetii infection. However, there is still a need to assess the specific contribution of cattle. Indeed, most seroprevalence studies in humans were carried out in areas comprising both cattle and small ruminants, the latter being systematically implicated in human Q fever outbreaks. Therefore, we conducted a cross-sectional study in areas where C. burnetii infection in cattle was endemic, where the density of cattle and small ruminant farms were respectively high and very low. The aim was to estimate the seroprevalence rates among two occupational (cattle farmers and livestock veterinarians), and one non-occupational (general adult population) risk groups. Sera were collected in 176 cattle farmers, 45 veterinarians and 347 blood donors, and tested for phase I and II antibodies using immunofluorescence assay. Seroprevalence rates were 56.3% among cattle farmers, 88.9% among veterinarians and 12.7% among blood donors. This suggests that a specific risk for acquiring C. burnetii infection from cattle in endemically infected areas exists, mainly for occupational risk groups, but also for the general population. Further research is needed to identify risk factors for C. burnetii infection in humans in such areas.